Long noncoding RNAs in bacterial infection. (14th May 2021) - Schmerer, Nils; Schulte, Leon N.
Abstract: Infectious and inflammatory diseases remain major causes of mortality and morbidity worldwide. To combat bacterial infections, the mammalian immune system employs a myriad of regulators, which secure the effective initiation of inflammatory responses while preventing pathologies due to overshooting immunity. Recently, the human genome has been shown to be pervasively transcribed and to generate thousands of still poorly characterized long noncoding RNAs (lncRNAs). A growing body of literature suggests that lncRNAs play important roles in the regulatory circuitries controlling innate and adaptive immune responses to bacterial pathogens. This review provides an overview of the roles of lncRNAs in the interaction of human and rodent host cells with bacterial pathogens. Further decoding of the lncRNA networks that underlie pathological inflammation and immune subversion could provide new insights into the host cell mechanisms and microbial strategies that determine the outcome of bacterial infections. This article is categorized under: RNA in Disease and Development > RNA in Disease RNA Interactions with Proteins and Other Molecules > Protein‐RNA Interactions: Functional Implications Abstract : To clear bacterial pathogens without undue tissue damage, the host must tightly balance its defense programs and anticipate bacterial virulence strategies. LncRNAs play a key role in this context.